Expectations, effectiveness and discrepancies: exploring multiple HR roles in the Chinese business context. Issue 10 (30th May 2016) - Gao, Zhonghua; Zhang, Yingying; Zhao, Chen; Li, Chaoping; Wu, Chunbo
Abstract : One of the strategic issues in human resource management (HRM) research is the recognition of HR professionals' roles, yet how effective HR professionals are performing these roles has seldom been studied. This article conducts a two-phase study to explore the role expectations, role effectiveness and discrepancies of HR professionals in the Chinese business context. In the first phase, six roles in three domains were determined using a qualitative method. In the second phase, hypotheses were proposed and tested empirically. The results highlight that the value of role effectiveness is significantly lower than that of role expectation. In terms of perceptive discrepancies between HR and non-HR individuals, significant differences exist on the expectations of the roles in the strategic domain (i.e. facilitator and supporter), and also on the effectiveness of the roles in all three domains, except for that of facilitator in the strategic domain. The results also indicate that the effectiveness of each different role has a distinctive weighting in explaining the overall effectiveness of HRM, and that different groups hold diverse views on the relationship between role effectiveness and overall effectiveness.